If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/43)*x+9/43 = 15/43 // - 15/43
(3/43)*x+9/43-(15/43) = 0
(3/43)*x+9/43-15/43 = 0
3/43*x-6/43 = 0 // + 6/43
3/43*x = 6/43 // : 3/43
x = 6/43/3/43
x = 2
x = 2
| 12m^2-3m=0 | | S+3/1/2s+20=47 | | .6(y-3)=.1y | | -3x-5y=-45 | | 7(x-3)=5(x-3) | | 7x+3=-3+5x+10 | | 9x^2-36+32=0 | | -43=-7-9x | | 4/3n^2+4n=-3 | | y=9mx+2b | | H=8(3.14)m | | 29+4/1/4 | | x(2x+0.15)+(x+0.05)=1.8 | | H(t)=-14t^2+200t | | w(w+6)+4w=7+w(w+9) | | 7ln(x+7)-9lnx=0 | | 5(x-3)=(x+4) | | v+9/4=8 | | 2w+2(w+4/1/4)=124/1/2 | | 12(x-4)+6=6 | | 5x-15/7x+21*4x+12/14x-42 | | 2x+1+x-7=180 | | 2(s-1)=16 | | -9=.6x-17 | | -3(1-8n)=93 | | 4+(5+8)=(5+8)+4 | | 4g+8=-27 | | 2w+2(a+4/1/4)=124/1/2 | | 6/r+7/r-4 | | 4(5-7m)=-92 | | x/6=43 | | -8b-(5b-2)=-89 |